2015
DOI: 10.1016/j.beth.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Group-Based CBT for Child Social Phobia: A Pilot Study

Abstract: Objective: Although CBT has proven efficacious in the treatment of child social phobia (SP), most children do not present for treatment and child SP may be less responsive to treatment than other anxiety disorders. Intensive, group-based, SP-specific CBT may improve the efficacy of, and access to, treatment for child SP. The aim of this study was to provide a preliminary examination of such a program. Method: Forty Australian children aged 7-12 years (15 male and 25 female) were allocated into treatment and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 61 publications
4
40
2
Order By: Relevance
“…Cognitive-behavioural therapy (CBT) is an efficacious treatment for treating anxiety disorders in children and adolescents (see and includes psychoeducation, somatic management, cognitive restructuring, and exposure therapy delivered Clinical Psychologist 22 (2018) [344][345][346][347][348][349][350][351][352][353][354] in either individual or group format (e.g., Kendall, 1994;Manassis et al, 2002;Silverman et al, 1999;Spence, Donovan, & Brechman-Toussaint, 2000). Although a number of studies utilising diagnosis-specific treatments have found promising results (e.g., Beidel, Turner, & Morris, 2000;Donovan, Cobham, Waters, & Occhipinti, 2015;Farrell, Waters, Milliner, & Ollendick, 2012;Ollendick et al, 2015;Pincus, Elkins, & Hardway, 2014;Spence et al, 2000), the vast majority of studies examining the efficacy of CBT have adopted a transdiagnostic approach by applying a common set of CBT principles to children with a range of anxiety disorders (cf. McEvoy, Nathan, & Norton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive-behavioural therapy (CBT) is an efficacious treatment for treating anxiety disorders in children and adolescents (see and includes psychoeducation, somatic management, cognitive restructuring, and exposure therapy delivered Clinical Psychologist 22 (2018) [344][345][346][347][348][349][350][351][352][353][354] in either individual or group format (e.g., Kendall, 1994;Manassis et al, 2002;Silverman et al, 1999;Spence, Donovan, & Brechman-Toussaint, 2000). Although a number of studies utilising diagnosis-specific treatments have found promising results (e.g., Beidel, Turner, & Morris, 2000;Donovan, Cobham, Waters, & Occhipinti, 2015;Farrell, Waters, Milliner, & Ollendick, 2012;Ollendick et al, 2015;Pincus, Elkins, & Hardway, 2014;Spence et al, 2000), the vast majority of studies examining the efficacy of CBT have adopted a transdiagnostic approach by applying a common set of CBT principles to children with a range of anxiety disorders (cf. McEvoy, Nathan, & Norton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Social anxiety disorder is a clinical problem characterized by anxiety about social situations in which people are faced with an assessment (1). Social anxiety disorder can be a very debilitating social relation.…”
Section: Introductionmentioning
confidence: 99%
“…Social phobia or social anxiety disorder (SAD) is a clinical pattern of the self-protective social behavior that concerns about provoking negative reactions such as criticism, being ridiculed, and treat others inappropriately (1). Social phobia is an anxiety disorder; it is a marked fear or anxiety about one or more social situations in which people are exposed to possible scrutiny by others (2). SAD can debilitate social relations and progress.…”
Section: Introductionmentioning
confidence: 99%